2008
DOI: 10.2138/am.2008.2757
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the Paso Robles soils on Mars

Abstract: Visible, near-infrared, thermal, and Mössbauer spectroscopic data from the exposed, bright track soil at the "Paso Robles" site within Gusev crater, Mars, indicate the presence of Fe 3+ -sulfates and possibly Fe 3+ -phosphates admixed with the host soil. When the spectroscopic analyses are combined with constraints imposed by chemical data, the determined dominant Fe 3+ -sulfate component is hydrous, and all of the spectroscopic methods suggest that it is probably ferricopiapite or some closely related, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 30 publications
(41 reference statements)
3
67
0
Order By: Relevance
“…[37] Ferricopiapite has also been suggested as the major sulfur-bearing constituent in Paso Robles salty soils by a study combining the Pancam, MB and MiniTES data from Spirit with laboratory experiments. [38] Ferricopiapite, fibroferrite and paracoquimbite are suggested by the spectral unmixing of Pancam images of soils in the Gusev crater. [39] These findings and investigations reinforce the importance of obtaining a better understanding of spectroscopic properties of the copiapite group of minerals through laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Ferricopiapite has also been suggested as the major sulfur-bearing constituent in Paso Robles salty soils by a study combining the Pancam, MB and MiniTES data from Spirit with laboratory experiments. [38] Ferricopiapite, fibroferrite and paracoquimbite are suggested by the spectral unmixing of Pancam images of soils in the Gusev crater. [39] These findings and investigations reinforce the importance of obtaining a better understanding of spectroscopic properties of the copiapite group of minerals through laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In this area, soil and rock that have 65-92 wt % silica have been observed by the Spirit rover [Ruff et al, 2011]. One such soil class, Paso Robles, has additional Fe and Mg sulfates [Lane et al, 2008;Yen et al, 2008]. Yen et al [2008] suggested that sulfur-rich volcanic gas and hydrothermal fluids altered local bedrock forming amorphous silica and hydrated Fe and Mg sulfates.…”
Section: Home Platementioning
confidence: 87%
“…Amorphous silica is also abundant, as well as iron phases including magnetite (Fe 3 O 4 ) and nanophase oxides [Squyres et al, 2007]. The Spirit rover wheels exposed additional opaline silica and ferric sulfates [Lane et al, 2008;Ruff et al, 2011]. Home Plate in Gusev crater is another area with abundant amorphous silica and sulfates suggesting hydrothermal precipitation from a hot spring or volcanic gas emissions (i.e., fumaroles) [e.g., Squyres et al, 2007;Yen et al, 2008;Ruff et al, 2011].…”
Section: Acid-sulfate Mineralogy Of Marsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data from the Martian exploration rovers and orbiters also show occurrence and distributions of various iron minerals on the Mars in local and global scale (Bandfield, 2002;McSween, 2002;McSween et al, 2003McSween et al, , 2009Rogers and Christensen, 2007;Lane et al, 2008;Rogers and Aharonson, 2008).…”
Section: Introductionmentioning
confidence: 96%